The Stability of Parental Bonding Reports: A 20-Year Follow-up - Murphy, Eleanor (2010)
BACKGROUND: Addressing the long-term reliability of retrospectively assessed parenting is underscored by the well-documented association between parenting behaviors, and mood disorders in offspring. The rarity of longitudinal research with follow-up periods exceeding 10 years creates a need for additional studies. METHODS: 134 offspring of depressed and non-depressed parents were assessed on Parental Bonding Instrument (PBI) scores, lifetime major depression (MDD), and current depressive symptoms at four waves across 20 years. PBI rank-order and mean level stability, individual trajectories, and the impact of baseline age, gender, and lifetime MDD on stability, were obtained using multiple regression and linear mixed model analyses. RESULTS: Besides paternal overprotection which showed a 1.6-point average decrease, the PBI domains remained non-significant for mean level change over 20 years. However, there was significant individual variation for all PBI domains. Lifetime MDD and age did not significantly impact retest correlations; older age at baseline was associated with higher average paternal overprotection. Sons had lower retest correlations than daughters, but did not differ from daughters on mean-level stability. Current depressive symptoms were associated with PBI scores, but did not impact the effect of lifetime MDD, gender or age on mean level stability and individual trajectories. LIMITATIONS: Small sample sizes and measuring lifetime MDD as present or absent may have restricted our ability to detect effects of MDD history on PBI stability. CONCLUSION: The PBI is a robust measure of an important environmental risk for depressive disorders, and can be variably sensitive to sample characteristics, the passage of time and mood fluctuations. However, this sensitivity does not appear to significantly bias the long term stability of this instrument.